Perinatal Propylthiouracil-Induced Hypothyroidism Impaired Motor Coordination in Adult Female Offspring - Miski A. Khairinisa; Yusuke Takatsuru; Izuki Amano; Michifumi Kokubo; Asahi Haijima; Wataru Miyazaki; Noriyuki Koibuchi (Pharmacology and Clinical Pharmacy Research)
Thyroid hormone (TH) play crucial roles in the growth and development of brain. Efficiency of TH during the perinatal period results in severe mental and physical retardation, known as cretinism in humans. Animal models have largely focused on mild and severe hypothyroidism associated with deficits in body weight, developmental delays, and cognitive deficits. Although various behavioral analyses have been reported, the effect of perinatal hypothyroidism in adult female mice has not been clarified. The aim of this study was to examine whether propylthiouracil (PTU)-induced hypothyroidism could impair motor coordination in female offspring. We used C57BL/6j mice and divided them into three groups based on the dose of PTU which was applied during perinatal period (embryonic day-14 to postnatal day-14); control, 5 ppm, and 50 ppm groups. We observed motor coordination function and additional nociceptive test in female offspring. We found that motor coordination and nociceptive threshold were affected in 50 ppm groups. We concluded that the moderate hypothyroidism could impair motor coordination in adult offspring.